Use of incinerated ash as a cement component in concrete: compressive strength modelling. Issue 12 (18th April 2018) - Lynn, Ciarán J.; Dhir, Ravindra K.; Ghataora, Gurmel S.
Abstract : This paper presents a model for the estimation of the compressive strength of concrete using incinerated ashes, municipal incinerated bottom ash and sewage sludge ash as an addition. Based on sourcing and systematic coordination of global data on this subject, an analysis of the properties of the ashes was undertaken. Collective data on the compressive strength performance of mortar and concrete mixes were also assessed. The strength model was then developed using a regression analysis approach, utilising the structure of the renowned Abram's law as the foundation, focusing specifically on the 28 d performance. The resultant model estimates can provide a greater focus for the initial trial testing undertaken when experimenting with the concrete mix design process with ashes. The model offers an informed view of how the properties of incinerated ash influence concrete strength, which can be useful for evaluating the quality of local ashes and avoiding unfavourable end-product performance.